Набат 3: [роман] / Александр Гера - Гера Александр Иванович (АСТ, 1999)
Экземпляры: ф.2 (2005) / Инвентарный номер: 49458 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Г 37 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44